PENGARUH NOISEMODULATED MONAURAL BEATS AUDITORY TERHADAP PENINGKATAN KAPASITAS MEMORI PADA LANSIA - Adre Mayza,* Shella,** Brian Manurung** (NEURONA, 2018)
INTRODUCTION MEMORY IMPAIRMENT IS ONE OF THE DISTURBANCES OF COGNITIVE FUNCTION THAT IS OFTEN FOUND AND INFLUENTIAL IN ELDERLY LIFE ACTIVITIES MEMORY IMPAIRMENT IN ELDERLY CAN BE IMPROVED BY APPLYING SEVERAL INTERVENTION MODES INCLUDING AUDITORY STIMULI BECAUSE BRAIN WAVES PLAY A ROLE IN DECREASING MEMORY FUNCTION IN THE ELDERLY